Islamic Religious Education Teacher’s Understanding of Minimum Competency Assessments and Their Implication for Learning - Khotimah, Husnul; Maemonah, Maemonah (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2022)
The Minimum Competency Assessment is a breakthrough in the new assessment system as a substitute for the National Examination. However, in reality, not a few teachers are stated to have not mastered the concept of this assessment model, so learning and assessment are not in line. So the purpose of this study is to identify teachers' understanding of Minimum Competency Assessment at the Elementary School level at the KKG PAI, Sukorejo District, and to find out the implications for PAI learning. The research used descriptive qualitative method. At the same time, the analysis technique applies Creswell's theory. The results of this study were teachers' understanding of the minimum competency assessment had understood the concept but had never applied the creation and processing of AKM-based questions. So it is necessary to have special training to provide teacher direction towards the progressiveness of educators in order to achieve educational goals. Meanwhile, the implications of a minimum competency assessment are the management of learning models, namely the application of contextual learning models integrated with technology and the readiness of learning materials and resources to improve literacy and numeracy abilities.